Exploring the potentialities of mobile technologies No teaching of Geography - Luiz Martins Junior; Josi Zanette Do Canto; Rosa Elisabete Militz Wypyczynski Martins (Universidade Federal de Rondônia, 2019)
The present text presents results of a specialization research that was developed in a Federal University of Santa Catarina that focused on the teaching of Geography and the use of mobile technologies. This study aimed to develop a collaborative mobile application as a strategy for the teaching of Geography in High School to solve the question: what are the contributions of the collaborative development of a mobile application for smartphones as an educational resource in the construction of geographic knowledge for the high school? The method was the one of the case study, with the participation of students of the High School of Basic Education of a school in the south of Brazil. Results indicate that pedagogical practice has helped students in the construction of geographical knowledge. The application Beyond the atmosphere, developed from the Application Factory, has demonstrated a potential resource for teaching and learning articulated to the subjects that enter the school space dominating different types of digital technologies. It allows rethinking and re-signification of teacher education in times and spaces declared digital.